TRICKLE DOWN THEORY SEBAGAI DASAR MOTIVASI MAHASISWA MELAKUKAN POLYTECHNIC SOSIAL RESPONSIBILITY - Tetty Rimenda; R. Elly Mirati (JOURNAL OF APPLIED BUSINESS ADMINISTRATION, 2019)
Initially CSR activities were known as corporate activities to pay attention to their environment. Further developments in CSR were also carried out at the University. This study discusses the CSR activities at the Jakarta State Polytechnic Social Responsibility, whose implementation is carried out through AGTV. This AGTV activity has been held for 6 years in Lio Depok Village. The problem faced is the lack of interest of volunteers to help implement this AGTV activity. The purpose of this study was to examine the effect of Trickle Down Theory which has been widely used in the field of fashion and promotion of the motivation to implement AGTV. Respondents were volunteers from the Jakarta State Polytechnic Accounting Department who carried out the Polytechnic Social Responsibility program. Data is processed by SPSS regression analysis. The results prove that Trickle Down and Trickle Up do not influence motivation in carrying out CSR activities, but the Trickle Round which is an attachment between volunteers influences the implementation of CSR carried out in AGTV